The Selection of Maxillary Anterior Teeth Width in Kashmiri Population - Nazir, Shazana; Zargar, Nazia Majeed; Khurshaid, Syed Zameer; Shah, Asim Farooq; Mir, Shazia; Rashid, Raisa (Journal of Orofacial Research, 2015)
Introduction: Determining the width of maxillary anterior teeth is a difficult aspect in complete denture fabrication. The width of maxillary anterior teeth is determined by taking various anatomical landmarks on the face as a guide, such as the interpupillary, interalar, intercommissure and interzygomatic distance, etc. The present clinical study was carried out to evaluate the relationships between maxillary anterior teeth measurements (canine to canine and central incisor width) and various horizontal facial parameters. Materials and methods: The facial and dental measurements were obtained directly from 60 Kashmiri  undergraduate dental students by using vernier calliper and dental floss. Result: Correlation analysis was done using Pearson’s correlation analysis and it was determined that the incisor width and canine to canine distance show positive correlation with some of the facial measurements. Conclusion: This study inferred that while most of the measurements showed a positive correlation with the incisor width and canine width in the different face forms none of them were found to be significant.